In Vitro Propagation of Buah Merah (Pandanus Conoideus Lam) Through Lateral Bud Proliferation - Imelda, Maria; Wulansari, Aida; Sumarnie, Sumarnie (BRIN, 2008)
Pandanus conoideus Lam or 'Buah merah' of the Pandanaceae is a native to East Indonesia, particularly Papua and North Maluku. Traditionally the fruits are used for health promotion and maintenance as well as for curing several illnesses. Recently, it has been reported that the fruit its are potential for cancer medication. As a result, there has been an overexploitation of the plants from their habitats. In order to anticipate their possible disappearance due to overexploitation in the wild, an efficient and effective technology for the mass propagation, conservation, and cultivation of these plant should be developed. Generally buah merah is propagated vegetatively by offshoots and stem cuttings or generatively by seeds. Micropropagation has many advantages over the conventional method because the technique allows mass clonal and pathogen-free production of plants at a high rate of multiplication all year round. In this research the effects of 0.1-0.2 mg/L thidiazuron (TDZ), 0.5-1.0 mg/L benzyl amino purine (BAP), and 0.25-0.5 mg/L kinetin (KN) on shoot bud induction and proliferation of P. conoideus were investigated using nodal infections or lateral buds of P. conoideus on modified Murashige and Skoog (MS) medium. Shoots were rooted on MS medium without plant growth regulator (PGR). The result showed that lateral bud of Pandanus start d to initiate growth after 4-7 days in culture. The best medium for shoot proliferation was MS containing either 0.5 mg/l BAP with 0.1 mg/l TDZ or 1 mg/l BAP with 0.5 mg/l KN giving a multiplication rate of 16.5 shootlets per shoot bud explant after 8 weeks. Rooting of shoots was successfully conducted on MS medium without PGR. Acclimatization of rooted plantlets was achieved on a mixed medium of cocopeat and soil (1:1).